The ANALISIS FAKTOR SOSIAL, BUDAYA, PRIBADI DAN PSIKOLOGIS TERHADAP KEPUTUSAN PEMBELIAN DI MODESHOP BALIKPAPAN - Marlindawaty Linda (Jurnal GeoEkonomi, 2022)
This research aims to analyze social, cultural, personal and psychological variables on purchasing decisions. Method of data collection through the distribution of questionnaires to all consumers who shop at Modeshop Balikpapan as the object of this research. Non probability sampling technique with a sample size of 100 respondents. This type of research is descriptive quantitative using classical assumption test and multiple linear regression through SPSS.V.20 statistical test tool. The results of this research, simultaneously social, cultural, personal and psychological variables influence to purchasing decisions at Modeshop Balikpapan and partially, personal  variables have a significant and dominant influence on consumer purchasing decisions at Modeshop Balikpapan.